Functional Signatures of Human CD4 and CD8 T Cell Responses to Mycobacterium tuberculosis - Prezzemolo, Teresa; Guggino, Giuliana; La Manna, Marco Pio; Di Liberto, Diana; Dieli, Francesco; Caccamo, Nadia (Frontiers in Immunology, 2014)
With 1.4 million deaths and 8.7 million new cases in 2011, tuberculosis (TB) remains a global health care problem and together with HIV and Malaria represents the one of the three infectious diseases world-wild. Control of the global TB epidemic has been impaired by the lack of an effective vaccine, by the emergence of drug-resistant forms of Mycobacterium tuberculosis (Mtb) and by the lack of sensitive and rapid diagnostics. It is estimated, by epidemiological reports, that one third of the world’s population is latently infected with Mtb, but the majority of infected individuals develops long-lived protective immunity, which controls and contains Mtb in a T cell-dependent manner. Development of TB disease results from interactions among the environment, the host, and the pathogen, and known risk factors include HIV coinfection, immunodeficiency, diabetes mellitus, overcrowding, malnutrition, and general poverty; therefore an effective T cell response determines whether the infection resolves or develops into clinically evident disease. Consequently, there is great interest in determining which T cells subsets mediate anti-mycobacterial immunity, delineating their effector functions. On the other hand, many aspects remain unsolved in understanding why some individuals are protected from Mtb infection while others go on to develop disease. Several studies have demonstrated that CD4+ T cells are involved in protection against Mtb, as supported by the evidence that CD4+ T cell depletion is responsible for Mtb reactivation in HIV-infected individuals. There are many subsets of CD4＋ T cells, such as T-helper 1 (Th1), Th2, Th17, and regulatory T cells (Tregs), and all these subsets cooperate or interfere with each other to control infection; the dominant subset may differ between active and latent Mtb infection cases. Mtb-specific CD4+ Th1 cell response is considered to have a protective role for the ability to produce cytokines such as IFN- or TNF- that contribute to